ANALISIS POTENSI PENINGGALAN SUMBER DAYA ARKEOLOGI DAN PEMANFAATANNYA SEBAGAI SUMBER BELAJAR SEJARAH SMA DI KABUPATEN BANYUWANGI - I Kadek Yudiana; Mahfud; Anggun Kuswinda Asih (Nusantara Hasana Journal, 2021)
Traces of past human life activities can be seen in cultural remains such as artifacts, features and ecofacs. The cultural remains found today are also referred to as archaeological resources. We have to explore the potential of these archaeological traces or remains so that we can bring them back as a learning resource. Banyuwangi Regency is rich in archaeological heritage that can be used as an alternative source of learning from existing books. This study tries to analyze these relics and present them into the history learning of senior high schools in Banyuwangi. The results show that the archaeological remains in Banyuwangi are very complete from prehistoric times to modern history. However, the history teacher at senior high school did not explore these relics with various obstacles, ranging from difficulties in integrating materials and financial problems which were large enough to invite students to places that had archaeological remains. This study provides an overview of the subject matter that can be integrated according to the 2013 curriculum and the findings of archaeological remains in Banyuwangi as a learning resource.